1979
DOI: 10.1002/sce.3730630210
|View full text |Cite
|
Sign up to set email alerts
|

Children's conceptions of heat and temperature

Abstract: If I had to reduce all of educational psychology to just one principle, 1 would say this:The most important single factor influencing learning is what the learner already knows. Ascertain this and teach him accordingly[ I , p vi]. IntroductionWith knowledge of what the learner brings to an instructional setting recognized as such a vital component in planning educational programs, it should have become an important stimulus to educational research. One area where this has been true in both science education an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
136
0
59

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(201 citation statements)
references
References 1 publication
6
136
0
59
Order By: Relevance
“…Decorre daí, que a representação vinculando água, sujeira e esquistossomose pode ter originado do conhecimento das doenças microbianas ou viróticas comuns, que são transmitidas pela água suja. Estudos (Erickson, 1979;Hewson et al, 1988) mostram que o grau de persistência do senso comum obstruindo o conhecimento científico, é associado a seu grau de universalidade.…”
Section: Resultsunclassified
“…Decorre daí, que a representação vinculando água, sujeira e esquistossomose pode ter originado do conhecimento das doenças microbianas ou viróticas comuns, que são transmitidas pela água suja. Estudos (Erickson, 1979;Hewson et al, 1988) mostram que o grau de persistência do senso comum obstruindo o conhecimento científico, é associado a seu grau de universalidade.…”
Section: Resultsunclassified
“…Interviews with 12-year-olds about four tasks relating to heat and temperature reveal a number of ideas that are scientifically incorrect (Erickson, 1979(Erickson, , 1980. Common alternative conceptions include that heat and cold are two different substances with matter-like properties and which can flow like fluids, and that temperature is a measure of how much heat (in the aforementioned substance manner) is contained in an object.…”
Section: Temperaturementioning
confidence: 99%
“…These studies have focused on certain concepts in mechanics (Clement, 1982;Halloun & Hestenes, 1985;McCloskey, 1983), electricity (McDermott &Shaffer, 1992; Shipstone, 1988), and heat and temperature (Erickson, 1979(Erickson, , 1980Rogan, 1988). Duit et al (2007) documented a bibliography of the publications on students" ideas in science and reported that mechanics (especially the force concept) and electricity (especially simple electric circuits) are over-researched domains in physics.…”
mentioning
confidence: 99%